PKH Shop sebagai Pemberdayaan Masyarakat untuk Meningkatkan Perekonomian Keluarga Prasejahtera Penerima Bantuan Sosial PKH Melalui Team Based Project Pejuang Muda Kementerian Sosial di Kecamatan Banjarsari Kabupaten Ciamis - Septian Cahya Azhari; Ely Satiyasih Rosali (Universitas Pahlawan Tuanku Tambusai, 2022)
The community empowerment program through the team-based project PKH Shop Pejuang Muda, Ciamis Regency, Ministry of Social Affairs of the Republic of Indonesia is an effort to provide skills and creativity to underprivileged communities in the hope of improving the standard of living or financial aspects of the community. Purpose This community service aims to empower underprivileged communities through the Ministry of Social's youth warrior program. Through the PKH Shop team-based project program, underprivileged communities who receive PKH social assistance are encouraged to be better, especially in terms of finance. The provision of entrepreneurship training along with funding for entrepreneurs is the main thing that must be given to be able to build and strengthen the entrepreneurial spirit of the community. The method used to obtain data using a descriptive qualitative approach. The result of this community service is to develop social entrepreneurship to help alleviate poverty in underprivileged communities. It is hoped that this community service will be able to become an example for other regions to empower underprivileged communities through social entrepreneurship.